Development of flexible supercapacitors using an inexpensive graphene/PEDOT/MnO2 sponge composite. (5th July 2017) - Moussa, Mahmoud; Shi, Ge; Wu, Hao; Zhao, Zhiheng; Voelcker, Nicolas H.; Losic, Dusan; Ma, Jun
Abstract: It remains a formidable challenge to develop supercapacitors having both high stretchability and electrochemical performance. A ternary polymer composite was herein developed by engineering graphene platelets (GnPs), poly (3, 4-ethylenedioxythiophene) (PEDOT) and manganese dioxide (MnO2 ) into a kitchen sponge. Cost-effective GnPs having an electrical conductivity of 1460 S cm − 1 were deposited onto the sponge pore surface by a simple dipping and drying process, followed by in situ polymerization of 3, 4-ethylenedioxythiophene. MnO2 was then deposited onto the GnPs and PEDOT layers through soaking the GnP/PEDOT sponge into KMnO4 solution. When the composite was used as the electrodes for a flexible, stretchable supercapacitor, we obtained not only high specific capacitance but a high stretchability up to 400%. The supercapacitor demonstrated a specific capacitance of 802.99 F g − 1 and an energy density of 55.76 Wh kg − 1, with 99% capacitance retention over 1000 stretching cycles; these are attributed to the synergy between the composite components as well as the wavy device structure. The mass and thickness of the MnO2 layer was found to increase with the soak, leading to the enhancement of electrochemical performance of GnP/PEDOT/MnO2 sponge electrodes, i.e. 368.96 F g − 1 for 5 min and 740.25 F g − 1 for 10 min. Graphical abstract: Graphene, PEDOT and MnO2 were deposited onto the pore surface of a sponge to create a stretchable supercapacitor. Highlights: A ternary composite was fabricated by layer-by-layer depositing graphene, PEDOT and MnO2 onto the pore surface of a sponge. The supercapacitor demonstrated a specific capacitance of 802.99 F g − 1 and an energy density of 55.76 Wh kg − 1 . Through a unique structural design, it achieved 99% capacitance retention over 1000 stretching cycles each at 400% strain.